Rebalancing the Vestibular System by Unidirectional Rotations in Patients With Chronic Vestibular Dysfunction - Sadeghi, Navid G.; Sabetazad, Bardia; Rassaian, Nayer; Sadeghi, Soroush G. (Frontiers in Neurology, 2019)
Vestibular dysfunction is a common disorder that results in debilitating symptoms. Even after full compensation, the vestibulo-ocular reflex (VOR) could be further improved by using rehabilitation exercises and visual-vestibular adaptation. Here, we describe a rehabilitation method that uses a unidirectional rotation in the dark (i.e., vestibular stimulation) toward the less active side (i.e., low response or LR side) in patients with chronic vestibular dysfunction. We show that the unidirectional rotation rebalances the activity in the vestibular pathway by increasing VOR responses during rotations in the LR direction and simultaneously decreasing the VOR for rotations in the high response (HR) direction. Originally, subjects had VOR asymmetry as measured by a high directional preponderance (DP). To study the short term effect, VOR responses to a sinusoidal rotation were measured before and 10, 40, and 70 min after a single unidirectional rotational rehabilitation session, which took ~ 7 minutes. We observed a significant decrease in VOR asymmetry at all times, as quantified by DP. Long term effects were studied in a second group of patients that were subjected to the rehabilitation 6 times over a 4 week period. Our results show a significant decrease in DP after rehabilitation, which occurred in the first 2 sessions in the majority of cases and was maintained for > 4 weeks in most cases. The improvement in DP over time was due to a decrease in VOR responses during HR rotations and an increase in the responses during LR rotations. Our results show that unidirectional rotation can significantly decrease asymmetries between the two sides even in chronically compensated patients and could be used as an effective supervised method for vestibular rehabilitation.